Role of endothelin-1 and its receptors, ET A and ET B , in the survival of human vascular endothelial cells - Mikhail, Marianne; Vachon, Pierre H.; D’Orléans-Juste, Pedro; Jacques, Danielle; Bkaily, Ghassan (Canadian journal of physiology and pharmacology, 2017)
Our previous work showed the presence of endothelin-1 (ET-1) receptors, ET A and ET B , in human vascular endothelial cells (hVECs). In this study, we wanted to verify whether ET-1 plays a role in the survival of hVECs via the activation of its receptors ET A and (or) ET B (ET A R and ET B R, respectively). Our results showed that treatment of hVECs with ET-1 prevented apoptosis induced by genistein, an effect that was mimicked by treatment with ET B R-specific agonist IRL1620. Furthermore, blockade of ET B R with the selective ET B R antagonist A-192621 prevented the anti-apoptotic effect of ET-1 in hVECs. However, activation of ET A receptor alone did not seem to contribute to the anti-apoptotic effect of ET-1. In addition, the anti-apoptotic effect of ET B R was found to be associated with caspase 3 inhibition and does not depend on the density of this type of receptor. In conclusion, our results showed that ET-1 possesses an anti-apoptotic effect in hVECs and that this effect is mediated, to a great extent, via the activation of ET B R. This study revealed a new role for ET B R in the survival of hVECs.